2022
DOI: 10.1158/2767-9764.crc-21-0148
|View full text |Cite
|
Sign up to set email alerts
|

Type-I Interferon Signaling Is Essential for Robust Metronomic Chemo-Immunogenic Tumor Regression in Murine Breast Cancer

Abstract: Many patients with breast cancer have a poor prognosis with limited therapeutic options. Here, we investigated the potential of chemo-immunogenic therapy as an avenue of treatment. We utilized two syngeneic mouse mammary tumor models, 4T1 and E0771, to examine the chemo-immunogenic potential of cyclophosphamide and the mechanistic contributions of cyclophosphamide-activated type-I interferon (IFN) signaling to therapeutic activity. Chemically-activated cyclophosphamide induced robust IFNα/β receptor-1-dependen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Earlier, Francia et al showed, in Her-2-positive human metastatic breast cancer xenografts, that the efficacy of trastuzumab was enhanced when combined with metronomic low-dose CTX [ 29 ]. Recent preclinical studies have used CTX combined with other drugs to treat breast cancer with varying success [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, Francia et al showed, in Her-2-positive human metastatic breast cancer xenografts, that the efficacy of trastuzumab was enhanced when combined with metronomic low-dose CTX [ 29 ]. Recent preclinical studies have used CTX combined with other drugs to treat breast cancer with varying success [ 30 ].…”
Section: Resultsmentioning
confidence: 99%